PENGARUH AUDIT TENURE, ROTASI AUDIT, FEE AUDIT DAN UKURAN PERUSAHAAN TERHADAP KUALITAS AUDIT PADA SEKTOR KEUANGAN PERIODE 2021-2023 - Shahadah, Eliza Nurul; Pabulo, Azfa Mutiara Ahmad (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study will examine the influence of audit tenure, audit rotation, audit fees, and company size on audit quality in the financial sector companies listed on the Indonesia Stock Exchange from 2021 to 2023. The study focuses on the importance of audit quality in maintaining public trust in financial statements, especially in the financial sector, which is crucial for controlling inflation, promoting growth, and ensuring economic stability. A logistic regression method within a quantitative framework is used for the analysis. A purposive sampling method was employed to select 37 companies from the financial industry for this study. The results indicate that audit fees and company size significantly affect audit quality. Thus, audits conducted by firms with greater resources and higher rates are more likely to yield positive outcomes. Conversely, audit rotation and audit tenure do not have a significant effect on audit quality. This study aims to achieve two objectives: first, to contribute to the growing body of academic research in the audit field; and second, to clarify the variables that influence audit quality.